Lacticaseibacillus rhamnosus GG Counteracts Rotavirus-Induced Ion Secretion and Enterocyte Damage by Inhibiting Oxidative Stress and Apoptosis Through Specific Effects of Living and Postbiotic Preparations - Buccigrossi, Vittoria; Poeta, Marco; Cioffi, Valentina; Terranova, Sara; Nunziata, Francesco; Lo Vecchio, Andrea; Guarino, Alfredo (Frontiers in Cellular and Infection Microbiology, 2022)
Background Administration of Lacticaseibacillus rhamnosus GG (LGG) to children with gastroenteritis is recommended by universal guidelines. Rotavirus (RV) causes diarrhea through combined cytotoxic and enterotoxic effects. Aim of this study was to evaluate the mechanisms of efficacy of LGG in an in-vitro model of RV diarrhea in its viable form (LGG) and conditioned medium (mLGG). Methods Ion secretion corresponding to the NSP4 enterotoxic effect, was evaluated by short circuit current (Isc) and the cytotoxic effect by transepithelial electrical resistance (TEER) in Ussing chambers, upon exposure to RV in Caco-2 enterocyte monolayers treated or not with living probiotic or its culture supernatant. Mechanisms of enterotoxic and cytotoxic damage were evaluated including oxidative stress measured by reactive oxygen species, apoptosis evaluated by DAPI and nuclear staining, NFkβ immunofluorescence. Results RV induced Isc increase and TEER decrease, respectively indicating ion secretion and epithelial damage, the two established pathways of diarrhea. Both probiotic preparations reduced both diarrheal effects, but their potency was different. Live LGG was equally effective on both enterotoxic and cytotoxic effect whereas mLGG was highly effective on ion secretion and showed minimal protective effects on cytoskeleton, apoptosis and NFkβ. Conclusions LGG counteracts RV-induced diarrhea by inhibiting both cytotoxic and enterotoxic pathogenic mechanisms. Namely, LGG inhibits chloride secretion by specific moieties secreted in the medium with a direct pharmacologic-like action. This is considered a postbiotic effect. Subsequently, live bacteria exert a probiotic effect protecting the enterocyte structure.